International law and the promotion of marine protected areas for the conservation of coral reef ecosystems - Goodwin, Edward J. (2006)
Coral reefs are one of the most beautiful natural habitats found on the Earth and one of the more productive. As a source of food, or as a basis for tourism, these formations support many local communities, industries and economies. Coral reefs also protect shorelines through dissipating the force of waves and act as a catalyst for the formation of land suitable for human habitation. However, like many other ecosystems, humans are increasingly placing coral reefs under intense pressure from pollution, unsustainable practices, and climate change. This thesis considers the measures international law is taking to tackle some of these threats to coral reefs through promoting one conservation strategy, namely marine protected areas. The analysis provided is based upon an investigation into developments under a number of global multilateral environmental agreements and, as such, is the first time treaties like the Ramsar Convention on Wetlands, the Convention on Biological Diversity, and the World Heritage Convention, have been considered in detail from this perspective. Ultimately we shall see how a number of initiatives are being pursued under international law which promote such enclave strategies in the marine environment for the conservation of these vital ecosystems.